(untitled) (Journal of Organizational Psychology, 2020)
The increased need for counseling services is evident with the steady rise in mental health conditions in college-aged students. However, a number of factors inhibit students from seeking help. This study argues that mental-health climates need to be assessed on individual campuses in order to improve counseling services outreach tactics. Results of surveys and interviews at Florida Institute of Technology suggest the awareness of mental health services and the availability of counseling staff need improvement. The presence of mental-health stigma and high levels of self-reliance among students would complicate the awareness improvement effort, but several measures could be effective.